Impact of Body Mass Index on Short-Term Outcomes in Patients Undergoing Percutaneous Coronary Intervention in Newfoundland and Labrador, Canada - Anne B. Gregory; Kendra K. Lester; Deborah M. Gregory; Laurie K. Twells; William K. Midodzi; Neil J. Pearce (Cardiology Research and Practice)
Background and Aim. Obesity (BMI ≥ 30 kg/m2) is associated with advanced cardiovascular disease requiring procedures such as percutaneous coronary intervention (PCI). Studies report better outcomes in obese patients having these procedures but results are conflicting or inconsistent. Newfoundland and Labrador (NL) has the highest rate of obesity in Canada. The aim of the study was to examine the relationship between BMI and vascular and nonvascular complications in patients undergoing PCI in NL. Methods. We studied 6473 patients identified in the APPROACH-NL database who underwent PCI from May 2006 to December 2013. BMI categories included normal, 18.5 ≤ BMI < 25.0 (n=1073); overweight, 25.0 ≤ BMI < 30 (n=2608); and obese, BMI ≥ 30.0 (n=2792). Results. Patients with obesity were younger and had a higher incidence of diabetes, hypertension, and family history of cardiac disease. Obese patients experienced less vascular complications (normal, overweight, and obese: 8.2%, 7.2%, and 5.3%, p=0.001). No significant differences were observed for in-lab (4.0%, 3.3%, and 3.1%, p=0.386) or postprocedural (1.0%, 0.8%, and 0.9%, p=0.725) nonvascular complications. After adjusting for covariates, BMI was not a significant factor associated with adverse outcomes. Conclusion. Overweight and obesity were not independent correlates of short-term vascular and nonvascular complications among patients undergoing PCI.